2016
DOI: 10.1007/s00125-016-4047-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel validated model for the prediction of insulin therapy initiation and adverse perinatal outcomes in women with gestational diabetes mellitus

Abstract: Aims/hypothesis Identifying women with gestational diabetes mellitus who are more likely to require insulin therapy vs medical nutrition therapy (MNT) alone would allow risk stratification and early triage to be incorporated into risk-based models of care. The aim of this study was to develop and validate a model to predict therapy type (MNT or MNT plus insulin [MNT+I]) for women with gestational diabetes mellitus (GDM). Methods Analysis was performed of de-identified prospectively collected data from women d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
89
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 61 publications
(107 citation statements)
references
References 12 publications
8
89
1
9
Order By: Relevance
“…Several studies have analyzed maternal characteristics (age, pre‐pregnancy BMI, ethnicity, or previous GDM) or biological parameters (FPG, HbA1c >5.4%, and elevated OGTT values) that should be associated with AIT . A large retrospective study analyzed outcomes according to pre‐pregnancy BMI categories (normal weight, overweight, and obese), and by diet or AIT and glycemic control .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have analyzed maternal characteristics (age, pre‐pregnancy BMI, ethnicity, or previous GDM) or biological parameters (FPG, HbA1c >5.4%, and elevated OGTT values) that should be associated with AIT . A large retrospective study analyzed outcomes according to pre‐pregnancy BMI categories (normal weight, overweight, and obese), and by diet or AIT and glycemic control .…”
Section: Discussionmentioning
confidence: 99%
“…In obese women with GDM, achievement of targeted levels of glycemia was associated with enhanced outcome only in women treated with insulin . Another large retrospective study in Australia with an ethnically diverse origin reported a model that correctly predicts AIT using seven dichotomized significant independent variables at diagnosis of GDM (age, pre‐pregnancy BMI, gestational age at diagnosis, FPG, HbA1c, family history of type 2 diabetes, and previous GDM) . The greater the number of predictors presented, the increased likelihood there was of requiring AIT …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations